EFFICIENCY OF CONSUMER DISPUTE SETTLEMENT AGENCY IN CONSUMER DISPUTE SETTLEMENT IN INDONESIA - Siddiq, Nakzim Khalid; Wahyuddin, Wahyuddin; Rahmatulloh, Johan (Faculty of Law Universitas Trunojoyo Madura, 2022)
The purpose of this study is to determine the legal protection of consumers by BPSK and the role of BPSK in consumer dispute resolution. This research is normative research, namely legal research that puts the law as a building norm system. The enactment of Law Number 8 of 1999, State Gazette of the Republic of Indonesia Number 42 of 1999 concerning Consumer Protection (UUPK) is a very significant development in the development of consumer protection law in Indonesia to create a just and prosperous society that is evenly material and spiritual in this era economic democracy based on Pancasila and the 1945 Constitution of the Republic of Indonesia. Based on the provisions of Article 45 paragraph (2) of the UUPK above, consumer dispute resolution can be pursued through the courts or out of court based on the voluntary choice of the disputing parties. Legal protection for consumers is important in maintaining the balance of legal relations between producers and consumers, so it is necessary to have principles of legal protection for consumers that can be a reference in protecting consumers. The results of the settlement of consumer disputes by means of consolidation, mediation, and arbitration are made in a written agreement signed by the consumer and the business actor concerned, further strengthened by the decision of the Assembly signed by the Chairman and members of the Assembly.